Breast Cancer Risk – Genes, Environment and Clinics - Fasching, P. A.; Ekici, A. B.; Adamietz, B. R.; Wachter, D. L.; Hein, A.; Bayer, C. M.; Häberle, L.; Loehberg, C. R.; Jud, S. M.; Heusinger, K.; Rübner, M.; Rauh, C.; Bani, M. R.; Lux, M. P.; Schulz-Wendtland, R.; Hartmann, A.; Beckmann, M. W. (Geburtshilfe und Frauenheilkunde, 2011)
The information available about breast cancer risk factors has increased dramatically during the last 10 years. In particular, studies of low-penetrance genes and mammographic density have improved our understanding of breast cancer risk. In addition, initial steps have been taken in investigating interactions between genes and environmental factors. This review concerns with actual data on this topic. Several genome-wide association studies (GWASs) with a case–control design, as well as large-scale validation studies, have identified and validated more than a dozen single nucleotide polymorphisms (SNPs) associated with breast cancer risk. They are located not only in or close to genes known to be involved in cancer pathogenesis, but also in genes not previously associated with breast cancer pathogenesis, or may even not be related to any genes. SNPs have also been identified that alter the lifetime risk in BRCA mutation carriers. With regard to nongenetic risk factors, studies of postmenopausal hormone replacement therapy (HRT) have revealed important information on how to weigh up the risks and benefits of HRT. Mammographic density (MD) has become an accepted and important breast cancer risk factor. Lifestyle and nutritional considerations have become an integral part of most studies of breast cancer risk, and some improvements have been made in this field as well. More than 10 years after the publication of the first breast cancer prevention studies with tamoxifen, other substances such as raloxifene and aromatase inhibitors have been investigated and have also been shown to have preventive potential. Finally, mammographic screening systems have been implemented in most Western countries during the last decade. These may be developed further by including more individualized methods of predicting the patientʼs breast cancer risk.
Keywords: BRCA (breast cancer antigen); breast; breast feeding; CAM (Complementary and Alternative medicine); cancer registry; estrogen receptor